Penerapan Metode “Gambus” Terhadap Peningkatan Kreativitas dan Kemandirian Siswa Pada Materi Bumi Sebagai Ruang Kehidupan - Sari, Fitri; Nuzliah, Nuzliah (Jurnal Nispatti, 2024)
his national character education innovation is entitled Application of the "Gambus" Method to Increase Student Creativity and Independence on the Earth as a Living Space Material. The author applies this GAMBUS method to the Earth as a living space material in class X IPS 1. This method is implemented in several stages, the first "Draw", students describe with their own ideas and creations, "Create", students make creativity from the imagination they produce in the picture into the form of learning products, the third stage is called "Serve", students present and present the results of the drawings they make into a product in front of the class. Creativity is a character that is expected in the implementation of this method, students are said to be creative if they are able to do something that produces a new activity obtained from the results of creative thinking by realizing it in the form of a new work. Creative students tend to be independent in their learning process. Independent students are able to learn in a place determined by themselves, at a time of their own choosing and by studying alone without face-to-face guidance from others so that they can more easily understand the subject matter. Based on the results of the implementation carried out, it was proven that student creativity increased by 83.3% and student independence in the material on the earth as a living space increased by 66.6%, thus having a good influence on student understanding of this material.